PAD TECHNIQUE ON DEFORESTATION SITUATION ON PETROPOLIS' METROPOLITAN AREA - RJ - Amanda Santos de Alencar; Thereza Cristina Ferreira Camello; Josimar Ribeiro de Almeida (Universidade do Estado do Rio de Janeiro, 2015)
With the rising and intensification of production's activities, as industries, the deforestation taxes show to be on an alarming level. It is wide spread known the consequences that deforestation might cause in metropolitan areas. In order to evalue the consequences of this growing phenomenon, is possible to use a role of ambiental impacts evaluations techniques. One of them is the Preliminary Analysis of Danger (PAD), which is based on qualitative and statistics analysis and might be used in association with other ambiental impacts evaluations techniques. It's goal is to analyze dangers in potential, it's causes and consequences, in which is also done an associated risk analysis, which the last is the association between the classifications of frequency and severity, and, in the end, it gives suggestions of measures to avoid these dangers (undesired events). In this study, six dangers have been identified, in which none of them present despicable or low risk (0%), 16% present medium or high risk and 66% present critic risk. These datas point out that the deforestation situation might cause dangers with great consequences to Petropolis' metropolitan area, just as floodings and earth slidings, which higthlights the urgency of management of the area.   DOI: http://dx.doi.org/10.12957/sustinere.2015.20003